Prevalence of early caries lesions in erupting permanent molars in Hue city - Le, Van Nhat Thang; Tran, Trong Dan; Nguyen, Thi Thuy Uyen; Nguyen, Thanh Minh; Hoang, Anh Dao; Tran, Tan Tai (Tạp chí Y Dược Huế, 2025)
Background: The difficult access to molars and the presence of gingival tissue on the occlusal surface during eruption can lead to dental caries. This study aims to determine the prevalence of early caries lesions in erupting permanent molars among schoolchildren aged 6 - 10 years in Hue city, Vietnam. Materials and methods: A cross-sectional study was conducted in 2023 to assess the status of early caries lesions in erupting permanent molars of 818 schoolchildren at primary schools in Hue city, using the International Caries Detection and Assessment System (ICDAS). Results: The rate of caries in permanent molars was 76.9% (53.6% of cases occurred in first molars), of which early caries accounted for 67.1% (36.0% of cases occurred in first molars). The prevalence of early caries lesions was higher in the mandibular molars than in the maxillary molars and significantly higher overall when considering the total caries rate. The left permanent mandibular first molar had the highest prevalence of early caries lesions (39.7%). In addition, among the erupting molars with early caries lesions, the first molar predominantly had ICDAS 2 (32.9%). Conclusion: The prevalence of early caries lesions in erupting permanent molars is high, with the permanent mandibular first molars being the most susceptible to influence.